2015
DOI: 10.1111/1462-2920.13019
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic and metaproteomic analyses of Accumulibacter phosphatis‐enriched floccular and granular biofilm

Abstract: Biofilms are ubiquitous in nature, forming diverse adherent microbial communities that perform a plethora of functions. Here we operated two laboratory-scale sequencing batch reactors enriched with Candidatus Accumulibacter phosphatis (Accumulibacter) performing enhanced biological phosphorus removal (EBPR). Reactors formed two distinct biofilms, one floccular biofilm, consisting of small, loose, microbial aggregates, and one granular biofilm, forming larger, dense, spherical aggregates. Using metagenomic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 86 publications
(123 reference statements)
3
30
1
1
Order By: Relevance
“…Only 32 proteins (3% of all identified proteins) showed significant fold changes, with P values of Ͻ0.05 (see Table S3 in the supplemental material). In comparison to other metaproteomic studies, where 10 to 15% of all identified proteins were significantly regulated (35,36), the number of regulated proteins in this study is distinctly small and implies a stable metaproteome profile of the rhizospheric community. Remarkably, more than 20% of these significantly regulated proteins were involved in PHA metabolism or the glyoxylate cycle and were also previously identified (25) (Fig.…”
Section: Resultscontrasting
confidence: 84%
“…Only 32 proteins (3% of all identified proteins) showed significant fold changes, with P values of Ͻ0.05 (see Table S3 in the supplemental material). In comparison to other metaproteomic studies, where 10 to 15% of all identified proteins were significantly regulated (35,36), the number of regulated proteins in this study is distinctly small and implies a stable metaproteome profile of the rhizospheric community. Remarkably, more than 20% of these significantly regulated proteins were involved in PHA metabolism or the glyoxylate cycle and were also previously identified (25) (Fig.…”
Section: Resultscontrasting
confidence: 84%
“…Here, isocitrate dehydrogenase was found NADP + dependent. This is consistent with the observation that most acetate consumers will use this conversion to produce NADPH for their anabolism (72) and confirms the protein annotation found in (64). Since PHA accumulation is now known to be NADH-preferring and without another sink of NADPH, the latter might accumulate anaerobically and thereby inhibit the isocitrate dehydrogenase reaction.…”
Section: Discussionsupporting
confidence: 92%
“…The discussion will be based on the observed high PAO enrichment of mainly Ca . Accumulibacter phosphatis clade I. Consequently, extrapolations of these results to Accumulibacter clade II or GAOs are speculative until further validation using respective environments for enrichments (10, 47, 6164).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, mass spectrometry based metaproteomic approaches are attracting particular attention for discovering microbial functions in mixed culture systems (Barr et al, 2015;Mosier et al, 2015;de Almeida et al, 2016;Salerno et al, 2016). mRNA levels can respond rapidly and sensitively to environmental conditions changes, while changes in protein abundances can be comparatively much slower (Zhu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%